The role of the accountant as a mediator in the communication process between companies and the tax authorities - Daciê , Franciele do Prado; Pieroli, Giovana Sartori Pieroli; Cortezia, Mara Cristina Piovesan (Seven Editora, 2023)
In the corporate environment, there is a constant need for information and accounting guidance. Thus, accounting can provide relevant information, and it is up to the accountant, as a mediator and conscientiator, to guide and support the relations between the entrepreneur and the tax authorities. Given this scenario, the objective of this research is to identify the guidance received by companies from their accountants to prevent tax evasion practices. To this end, descriptive and qualitative research was carried out, carried out with the use of a questionnaire, directed to fifty entrepreneurs, who take accounting services. Given the results, it is noticeable the growing participation of women in important positions within companies. There is also an increase in entrepreneurs who have undergraduate and graduate degrees. It is observed that most companies receive guidance from their accountants on the care that must be taken to avoid potential transaction costs in the relations between the tax authorities and the company – for example, fines and fines for evasion, delivery of ancillary statements, and the like. The results indicate that accountants are doing their role of guiding and supporting accounting information. However, it is believed that the managerial aspects can be improved through formal or informal meetings that include not only the fiscal portion of their services.  The overall satisfaction of respondents points out that most business owners are satisfied with the accounting support offered by their accounting offices. That said, it is clear that communication is fundamental in any type of business. With dialogue, contracts are less susceptible to errors, consequently generating fewer transaction costs, given that the supposed limited rationality will be remedied during meetings. DOI:https://doi.org/10.56238/devopinterscie-197